EDUTACH PORTAL AS A WEB FOR EDUCATION - SITÁŠ, Juraj; BELICA, Jozef (Trends in education, 2010)
Technical realization of modern education with on-line tools can take many forms. Web site we chose as the basis for building a EduTech Portal project, whose task was to create a Web site with material on the subject of methodological techniques.
Keywords: EduTech Portal; web; technics subject.